The Sage handbook of digital technology research - Price, Sara; Jewitt, Carey; Brown, Barry, 1972- (Los Angeles : Sage Publications Ltd., 2013)
Providing readers with an expansive and international overview, this handbook is the ideal resource on this fast-paced and ubiquitous field.
'Research on and with digital technologies is everywhere today. This timely, authoritative Handbook explores the issues of rapid technological development, social change, and the ubiquity of computing technologies that have become an integral part of people's everyday lives. This is a comprehensive, up-to-date resource for the twenty-first century. It addresses the key aspects of research within the digital technology field and provides a clear framework for readers wanting to navigate the changeable currents of digital innovation.' -- Back cover.
Notes on the editors and contributors -- Part 1 : An introduction to the field of contemporary digital technology research -- The historical context / Paul Ceruzzi -- The field of digital technology research / Charles Crook -- Part 2 : New digital technologies : key characteristics and consideration -- Context, location, and mobility : a human story / Matt Jones -- Online information : access, search and exchange / Gary Hsieh and Nicolas Friederici -- Social media, human connectivity and psychological well-being / Sonja Baumer -- Engaging practices : doing personalized media / Heather A. Horst and Larissa Hjorth -- Ethics, phenomenology and ontology / Anna Kouppanou and Paul Standish -- Part 3 : Research perspectives for digital technologies : theory and analysis -- Critical theory of technology / Sara M. Grimes and Andrew Feenberg -- Critical and cultural approaches to HCI / Jeffrey Bardzell -- Theories of embodiment in HCI / Paul Marshall and Eva Hornecker -- Space and place in digital technology research : a theoretical overview / Luigina Ciolfi -- Affect and experiential approaches / Kristina Hook -- Ethnographic approaches to digital research / Barry Brown -- The mediational perspective on digital technology : understanding the interplay between technology, mind and action / Victor Kaptelinin -- Ethnomethodology and conversation analysis : empirical approaches to the study of digital technology in action / Robert J. Moore -- Behavioral trace data for analyzing online communities / Cliff Lampe -- Multimodal methods for researching digital technologies / Carey Jewitt -- Projection, place, and point-of-view in research through design / Steven Dow, Wendy Ju and Wendy Mackay -- Design research : observing critical design / Laural Swan and Kirsten Boehner -- Part 4 : Environments and tools for digital research -- Tangibles : technologies and interaction for learning / Sara Price -- Material computing : integrating technology into the material world / Leah Buechley -- Haptic interfaces / Eve Hoggan -- Contrasting lab-based and in-the-wild studies for evaluating multi-user technologies / Yvonne Roger, Nicola Yuill and Paul Marshall -- Ubiquitous virtual reality environments / Yoosoo Oh and Woontack Woo -- Location-based environments and technologies / Ty Hollett and Kevin M. Leander -- Mobile learning in the majority world : a critique of the GSMA's position / Niall Winters -- Online and internet-based technologies : gaming / Catherine Beavis -- Online and internet-based technologies : social networking / Kirsty Young -- Learner modelled environments / Kaska Porayska-Pomsta and Sara Bernardini -- The interplay between research and industry : HCI and grounded innovation / Lars Erik Holmquist -- Afterword: looking to the future / Sara Price, Carey Jewitt and Barry Brown -- Index.
Includes bibliographical references and index.
Keywords: Human-computer interaction -- Research; Digital electronics -- Research